The Effect of Combining Visual Training with Drills on Football Players' Dribbling Skills - Muhamad Saep Apendi; Dede Rohmat Nurjaya; Yudi Nurcahya (ACTIVE: Journal of Physical Education, Sport, Health and Recreation, 2025)
This study aims to determine the effect of a combination of visual training and drills on the dribbling skills of 15-year-old football players at Football Academy Perbi. Dribbling is an important basic technique in football that requires the integration of motor, perceptual, and cognitive abilities. Visual training plays a role in improving perception, focus, and decision-making, while drills serve to strengthen basic techniques through structured repetition. The research method used was an experiment with a one-group pretest-posttest design involving 17 players. The measurement instrument used was a dribbling test. The training program was given for four weeks with a frequency of three times per week. The results showed a significant increase in dribbling skills after the treatment was given. The results of the paired sample t-test showed a significance value (Sig. 2-tailed) of 0.000 < 0.05, which means there was a significant difference between the pretest and posttest scores. The average dribbling time decreased from 23.17 seconds to 19.54 seconds. Thus, the combination of visual training and drills has been proven to have a significant effect on improving the dribbling skills of young football players.